Biological control of bacterial leaf blight (BLB) in rice–A sustainable approach - Bestha Sai Teja; Gayatri Jamwal; Vishal Gupta; Mansi Verma; Ayushi Sharma; Akash Sharma; Vinod Pandit (Heliyon)
Bacterial leaf blight (BLB) in rice, caused by the pathogen Xanthomonas oryzae pv. oryzae, is a significant agricultural problem managed through chemical control and cultivating rice varieties with inherent resistance to the bacterial pathogen. Research has highlighted the potential of using antagonistic microbes which can suppress the BLB pathogen through the production of secondary metabolites like siderophores, rhamnolipids, and hydroxy-alkylquinolines offering a sustainable alternative for BLB management. Additionally, the induction of plant immunity and defense-related enzymes in rice further enhances the resistance against the disease. Therefore, implementation of biological controls can complement chemical treatments in contributing towards the sustainability of rice production systems by aiming at host immunity improvement and killing of pathogen. It is crucial to continue exploring and understanding the complex interactions between various beneficial microbes, the rice plants, and the BLB pathogen to optimize and implement effective biocontrol strategies in future.